SOCIO-ECONOMIC AND STATISTICAL PERSPECTIVES ON WOMEN ENTREPRENEURS: CHALLENGES AND OPPORTUNITIES IN PUNJAB, INDIA - Talwar, Palak; Banga, Gagandeep (International Journal of Engineering Technologies and Management Research, 2025)
Women entrepreneurs in India face numerous challenges that hinder their ability to establish and grow successful businesses. Key obstacles include financial constraints, socio-cultural barriers, limited access to markets, skill and educational gaps, and inadequate policy and institutional support. Restricted access to capital, often due to gender biases and lack of collateral, severely limits their entrepreneurial opportunities. Societal expectations and traditional gender roles further exacerbate these challenges by imposing additional domestic responsibilities and reducing community support. Furthermore, inadequate marketing networks and a lack of business skills, coupled with ineffective implementation of supportive policies, restrict the growth and sustainability of women-led enterprises. Addressing these issues requires a comprehensive approach, including policy reforms, targeted financial initiatives, skill development programs, and fostering societal changes to promote gender equality. Empowering women entrepreneurs is essential for fostering inclusive economic growth and unlocking India's entrepreneurial potential.